2022
DOI: 10.1002/adhm.202200382
|View full text |Cite|
|
Sign up to set email alerts
|

Low Surface Accessible Area NanoCoral TiO2 for the Reduction of Foreign Body Reaction During Implantation

Abstract: The entry of implants triggers the secretion of damage associated molecular patterns (DAMPs) that recruit dendritic cells (DCs) and results in subsequent foreign body reaction (FBR). Though several studies have illustrated that the surface accessible area (SAA) of implants plays a key role in the process of DAMPs release and absorption, the effect of SAA on the immune reaction still remains unknown. Here, a series of TiO 2 plates with different SAA is fabricated to investigate the relationship between SAA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Molecular Dynamics: According to previous studies, [49] the molecular dynamics simulations of protein adhesion were performed by the GRO-MACS 2016.4 package with the charmm36 force field. The 3D structures of HMGB1 and FN-III 9-10 were obtained from the Protein Data Bank (PDB ID: 5ZE0; PDB ID: 1FNF).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular Dynamics: According to previous studies, [49] the molecular dynamics simulations of protein adhesion were performed by the GRO-MACS 2016.4 package with the charmm36 force field. The 3D structures of HMGB1 and FN-III 9-10 were obtained from the Protein Data Bank (PDB ID: 5ZE0; PDB ID: 1FNF).…”
Section: Methodsmentioning
confidence: 99%
“…[46,47] After reaching equilibrium in solution, Fn and HMGB1 with calcium phosphate (CaP) ceramic surface models were placed in a unified virtual box according to a previous research method. [48,49] The final system was used to simulate the adsorption of Fn and HMGB1 on CaP ceramic surfaces under experimental conditions (Figure 4A). The whole process was simulated in 10 ns, and root mean square deviation (RMSD results showed that the interaction between protein and CaP ceramics reached an equilibrium state at 2.5 ns (Figure S7A, Supporting Information).…”
Section: Molecular Dynamics Simulations Suggest That Hmgb1 Cannot Be ...mentioning
confidence: 99%
“…[70] The surface accessible area has been recognized as a factor that is involved in the initiation of FBR, therefore, the TiO 2 substrate with surface accessible area was fabricated, and it showed less cysteine residue exposure which reduced the activation of TLR4 and Myd88/TRAF6, thus inhibiting the NF-𝜅B signaling pathway and preventing FBR. [71] Stainless steel, owing to its affordability, ease of processing, and exceptional mechanical stiffness, has been one of the earliest materials employed for surgical implants. However, previous studies have reported that both stainless steel and its corrosion products can lead to inflammation, cell apoptosis, reduced cell viability, and impaired differentiation ability.…”
Section: Metallic Materialsmentioning
confidence: 99%
“…When ICD of tumor cells occurs, high mobility group box 1 (HMGB1) will be released from the nucleus and adenosine triphosphate (ATP) will be secreted from the cytoplasm. HMGB1 could promote the activation of DCs to phagocytose apoptotic tumor cells, 24 bind toll-like receptor 4 (TLR4) to facilitate DC maturation, and enhance antigen presentation to cytotoxic T lymphocytes (CTLs). 25 While ATP could stimulate the infiltration of CTLs in the tumor microenvironment, 26 chemotherapeutic drug-induced damage of DNA could also enhance cGAS-STING-mediated type I interferon (IFN) response to activate anti-tumor immune responses.…”
Section: ■ Introductionmentioning
confidence: 99%
“…When ICD of tumor cells occurs, high mobility group box 1 (HMGB1) will be released from the nucleus and adenosine triphosphate (ATP) will be secreted from the cytoplasm. HMGB1 could promote the activation of DCs to phagocytose apoptotic tumor cells, bind toll-like receptor 4 (TLR4) to facilitate DC maturation, and enhance antigen presentation to cytotoxic T lymphocytes (CTLs) . While ATP could stimulate the infiltration of CTLs in the tumor microenvironment, chemotherapeutic drug-induced damage of DNA could also enhance cGAS-STING-mediated type I interferon (IFN) response to activate anti-tumor immune responses. , At the same time, ICD could enhance the translocation of CRT molecules, an “eat me” pro-phagocytosis signal that interacts with the low-density lipoprotein receptor-related protein 1 (LRP1), facilitating its recognition by professional antigen-presenting cells (APCs) and acting as a critical molecular component in promoting ICD to the plasma membrane of tumor cells, which could induce tumor-associated macrophages (M2 phenotype) to transform into a phenotype with antitumor activity (M1 phenotype). , Hence, not only will the strategy that combines the CD47 blockade with chemotherapy-induced ICD significantly improve anticancer therapeutic efficacy but also considerably increase the beneficiary population of immunotherapy.…”
Section: Introductionmentioning
confidence: 99%